Hydrogen-resistant coating as well as preparation method and application thereof

By preparing a hydrogen-resistance coating composed of conductive two-dimensional material and electrocatalyst powder within the range of 55 to 75°C, the problem of inapplicability of hydrogen-resistance coating in the prior art is solved, and the effect of effectively blocking hydrogen atom penetration in the service environment of conventional metal materials is achieved.

CN119570295APending Publication Date: 2025-03-07WUHAN UNIV OF SCI & TECH

Patent Information

Application Number
CN202411696275.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing hydrogen-resistance coatings are not suitable in water/wet environments, and the preparation process requires high temperatures, making it difficult to adapt to the service environment of conventional metal materials.

Method used

A hydrogen-resistance coating made of conductive two-dimensional materials and electrocatalyst powder is used, which includes graphene, etc. The electrocatalyst powder is a transition metal carbide, such as MoC or WC, and is prepared in the range of 55 to 75°C by spraying or drop coating.

Benefits of technology

This coating can maintain the performance of blocking hydrogen atom penetration for a long time in a water/wet environment, and has a simple process and energy saving. It is suitable for service environments of conventional metal materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005152153050000011
    Figure HDA0005152153050000011
  • Figure HDA0005152153050000012
    Figure HDA0005152153050000012
  • Figure HDA0005152153050000013
    Figure HDA0005152153050000013
Patent Text Reader

Abstract

The invention discloses a hydrogen-resistant coating as well as a preparation method and application thereof. The hydrogen-resistant coating comprises a first coating and a second coating which are sequentially formed on the surface of the metal matrix, the first coating is composed of stacked conductive two-dimensional materials, and the conductive two-dimensional materials comprise one or more of graphene, graphene oxide and reduced graphene oxide; the second coating is prepared from electrocatalyst powder, dispersion liquid and a binder, and the electrocatalyst powder is transition metal carbide. The invention provides a hydrogen-resistant coating which can fully utilize a cathode protection system of a metal structure and reduce hydrogen atom permeation in a metal service process in a conventional water / wet environment. The hydrogen-resistant coating has the advantages that the structure is simple, the preparation process is simple, the hydrogen-resistant coating can be prepared within the temperature range of 55-75 DEG C, energy is saved, an existing cathode protection system and an electrocatalyst technology are fully utilized, gathering of hydrogen atoms on the surface of the coating is reduced, and the performance of blocking permeation of the hydrogen atoms can be kept for a long time in a water / wet environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen barrier materials, and in particular relates to a hydrogen barrier coating and a preparation method and application thereof. Background Art

[0002] In the engineering field, cathodic protection and coating are generally coupled to protect the metal substrate in service. Although this method can significantly inhibit metal corrosion, it is difficult to resist the "external hydrogen" in the environment from penetrating into the metal matrix to produce hydrogen damage. Hydrogen damage refers to the phenomenon that after hydrogen atoms penetrate into the metal matrix, the service performance of the metal is severely reduced or even destroyed. Once hydrogen damage occurs, it is extremely difficult to reverse. Therefore, it is particularly important to reduce the amount of hydrogen atom penetration and reduce the probability of hydrogen damage during the use of the metal. At present, there are many methods to slow down hydrogen damage, and hydrogen barrier coating is one of them.

[0003] At present, hydrogen barrier coatings are mainly concentrated in the following types. ① Use oxide coatings. For example: prepare an α-Al2O3 hydrogen penetration-resistant and corrosion-resistant insulating layer (201510440509.2, 201810737216.4); use stainless steel-based chromium oxide / manganese chromium spinel / aluminum oxide composite materials to prepare hydrogen barrier coatings (201210449522.0); prepare Y2O3 / TiO2 hydrogen penetration-resistant composite coatings on pipe fittings (202211707563.5); use multi-layer composite coatings to prevent hydrogen / deuterium / tritium penetration, each layer is composed of Al2O3, Cr2O3 and ZrO2 three-phase composites (202210648734.5). ② Use nitride coatings. For example: titanium nitride hydrogen penetration barrier coating is obtained by multi-arc ion plating on the surface of high-strength steel (202310661466.5); hydrogen barrier coating is prepared by composite nitride coating on the surface of carbon steel, such as CrN, TiN, AlN, etc. (202311699015.7). ③ Use two-dimensional material / nanomaterial coating. For example: in-situ self-grown large-size nanosheet reinforced and toughened hydrogen penetration barrier coating suitable for fusion reactor blanket module structural materials and hydrogen storage devices (202311660637.9). The working principle of hydrogen barrier coatings prepared using these materials is to increase the diffusion path of hydrogen atoms and increase the diffusion activation energy of hydrogen atoms inside the coating, making it difficult for hydrogen atoms to penetrate the hydrogen barrier coating. The preparation process of these hydrogen barrier coatings basically involves high temperature, and they are mostly used in complex environments such as gas, high temperature, and radiation; at the same time, these hydrogen barrier coatings are not suitable for the conventional service environment of metal structures, such as humid soil, low-temperature marine environment, etc., that is, the existing metal material hydrogen barrier coatings are relatively lacking in water / wet environments.

[0004] Some scholars have also added rare earth element La to X70 pipeline steel to reduce the adsorption and penetration of hydrogen atoms after it produces a rust layer (Zhengyi Xu, Pengyuan Zhang, Bo Zhang, et al. Journal of Industrial and Engineering Chemistry 122 (2023) 459-471.); or added rare earth (La, Ce) corrosion inhibitors to the service environment of X70 pipeline steel and adsorbed them on the surface of steel to produce a surface layer to reduce the adsorption and penetration of hydrogen atoms (Zhengyi Xu, Pengyuan Zhang, Bo Zhang, et al. Electrochimica Acta 425 (2022) 140734.). However, these are not coatings, and are not applicable to most existing conventional metal materials.

[0005] Therefore, there is an urgent need to provide a hydrogen barrier coating that is suitable for water / wet environments, can be prepared at low temperatures and has a simple process. Summary of the invention

[0006] The main purpose of the present invention is to address the problems and shortcomings of the prior art and to provide a hydrogen barrier coating with a simple structure, which can be prepared within the range of 55 to 75°C and can maintain the performance of blocking hydrogen atom penetration for a long time in a water / wet environment, as well as a preparation method and application thereof.

[0007] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0008] A hydrogen barrier coating comprises a first coating and a second coating sequentially formed on the surface of a metal substrate, wherein the first coating is composed of a stacked conductive two-dimensional material, wherein the conductive two-dimensional material comprises one or more of graphene, graphene oxide, and reduced graphene oxide, and the second coating is prepared from an electrocatalyst powder, a dispersion, and a binder, wherein the electrocatalyst powder is a transition metal carbide.

[0009] In the above solution, the electrocatalyst powder is MoC or WC.

[0010] In the above scheme, the dispersant is one or both of isopropanol and water.

[0011] In the above solution, the binder is perfluorosulfonic acid polytetrafluoroethylene copolymer.

[0012] The method for preparing the hydrogen barrier coating comprises the following steps:

[0013] Dispersing the conductive two-dimensional material in water to form a suspension, coating the suspension on the surface of the metal substrate, and drying to form a first coating;

[0014] The electrocatalyst powder, dispersion and binder are mixed and coated on the surface of the first coating layer, and then dried to form a second coating layer.

[0015] The above scheme also includes the step of pre-treating the metal substrate, wherein the pre-treatment includes degreasing, grinding and cleaning the surface of the metal substrate.

[0016] In the above scheme, the concentration of the suspension is 8-9 mg / mL.

[0017] In the above scheme, the suspension is coated on the surface of the metal substrate by spraying, dripping or spin coating.

[0018] In the above scheme, the drying temperature for forming the first coating is 60-70° C. and the time is 3-5 hours.

[0019] In the above scheme, the drying temperature for forming the second coating is 55-65° C. and the time is 1-2 hours.

[0020] In the above scheme, the concentration of the binder solution is 4.5% to 5.5%, and the volume ratio of the binder solution to the dispersion is 1:95 to 105.

[0021] In the above scheme, the dispersion liquid is a mixture of isopropanol and water in a volume ratio of 8.5 to 9.5:1.

[0022] In the above scheme, the electrocatalyst powder, the dispersion and the binder are mixed by ultrasonic oscillation, wherein the ultrasonic oscillation power is 120W and the time is 25 to 35 minutes.

[0023] In the above solution, the thickness of the first coating layer is 40-50 μm, and the thickness of the second coating layer is 0.5-1.5 μm.

[0024] In the above scheme, the ratio of the mass of the electrocatalyst powder to the volume of the dispersion liquid is 5.5-6.5 mg:1 mL.

[0025] The application of the hydrogen barrier coating is to connect the prepared metal substrate of the hydrogen barrier coating to the cathodic protection system and load the cathodic protection current.

[0026] In the above scheme, the cathodic protection current density is 10-50 mA / cm 2 .

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a hydrogen barrier coating that can fully utilize the cathodic protection system of the metal structure in a conventional water / wet environment and reduce the penetration of hydrogen atoms in the metal during service. The advantages are that the hydrogen barrier coating has a simple structure, a simple preparation process, can be prepared within the range of 55 to 75°C, saves energy, and fully utilizes the existing cathodic protection system and electrocatalyst technology to reduce the accumulation of hydrogen atoms on the coating surface, and can maintain the performance of blocking hydrogen atom penetration for a long time in a water / wet environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the structure of the hydrogen barrier coating provided in Example 1.

[0029] Figure 2 Electrochemical hydrogen permeation curves of Examples 1-2 and Comparative Examples 1-3.

[0030] Figure 3 Samples with different coatings: (a) X80 steel sample; (b) X80 steel + conductive resistive hydrogen layer sample; (c) X80 steel + electrocatalyst layer sample; (d) X80 steel + conductive resistive hydrogen layer + electrocatalyst layer sample. DETAILED DESCRIPTION

[0031] The principles and features of the present invention are described below in conjunction with examples, which are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, it is worth noting that the raw materials involved in the present invention are all common commercial products unless otherwise specified.

[0032] Example 1

[0033] like Figure 1 As shown, it is a hydrogen barrier coating provided in this embodiment, and the hydrogen barrier coating includes a first coating 2 and a second coating 3 formed sequentially on the surface of a metal substrate 1. The first coating 2 is composed of a multilayer stacked conductive two-dimensional material, and the conductive two-dimensional material includes one or more of graphene, graphene oxide, and reduced graphene oxide. The second coating 3 is prepared from an electrocatalyst powder, a dispersion and a binder. The electrocatalyst powder is a transition metal carbide, and the transition metal carbide is MoC or WC. The dispersion is a mixture of one or both of isopropanol or water. The metal substrate 1 can be pipeline steel, and can also be steel for offshore platforms, stainless steel, etc.

[0034] In this embodiment, the metal substrate 1 is X80 pipeline steel, the conductive two-dimensional material is graphene oxide, and the electrocatalyst powder, dispersion liquid and binder are MoC, isopropanol and water, and perfluorosulfonic acid polytetrafluoroethylene copolymer. It can be understood that pipeline steel is not limited to X80, and can also be X42, X52, X60, X70, X100, X120, etc.

[0035] This embodiment also provides a method for preparing the hydrogen barrier coating, the specific steps are:

[0036] X80 pipeline steel was cut into sheets of 20mm×20mm×1.5mm, sanded to 2000# with sandpaper, and then cleaned and dried. Then graphene oxide suspension was sprayed on the surface of X80 and dried in an oven to obtain a first coating. Then, electrocatalyst powder, dispersion and binder were mixed and coated on the surface of the first coating, and dried to form a second coating.

[0037] In this embodiment, the graphene oxide suspension is sprayed 10 times to obtain a first coating layer of 10 layers of conductive two-dimensional material. It is understandable that the number of layers is not limited to 10, as long as the thickness of the first coating layer is 40-50 μm.

[0038] The concentration of the sprayed graphene oxide suspension is 8.5 mg / mL, the oven drying temperature for drying the first coating is 65°C, the time is 3 hours, and the thickness of the first coating is 40-50 μm; in the second coating, the electrocatalyst powder is 6 mg of MoC, 1 mL of isopropanol and water (volume ratio 9:1) dispersion is added, and then 10 μL of perfluorosulfonic acid polytetrafluoroethylene copolymer binder (concentration 5wt%) solution is added, the ultrasonic oscillation power is 120 W, the time is 30 min, the oven temperature for drying the second coating is 60°C, the time is 2 h, and the thickness of the second coating is 0.5-1.5 μm. At this time, the obtained sample is as follows Figure 3 (d) as shown.

[0039] The experiment used a Davanathan-Stachursky double electrolytic cell. The sample was fixed between the cathode chamber and the anode chamber. The effective detection area was 1 cm 2 , the side with the second coating faces the cathode chamber. On the anode chamber side, a three-electrode system is used, with the sample as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the auxiliary electrode, connected to the electrochemical workstation by a wire; on the cathode chamber side, a two-electrode method is used, with the sample as the cathode and the platinum sheet as the anode.

[0040] During the experiment, 0.1 mol / L sodium hydroxide solution without dissolved oxygen was first loaded into the anode chamber, and the anode potential was controlled to be open circuit potential + 250 mV (relative to the reference electrode). When the background current measured in the anode chamber was less than 0.1 μA / cm 2 When the cathode chamber is filled with 0.1 mol / L sulfuric acid solution, a current of 10 mA / cm2 is applied between the positive and negative electrodes. 2After applying current to the cathode chamber, the hydrogen atom oxidation current in the anode chamber is recorded by the electrochemical workstation to obtain the electrochemical hydrogen permeation curve. The steady-state section of the curve is positively correlated with the hydrogen atoms that pass through the hydrogen barrier coating, that is, the lower the value of the steady-state section of the curve, the less hydrogen atoms penetrate the hydrogen barrier coating, and the better the effect of the hydrogen barrier coating.

[0041] At this time, the measured electrochemical hydrogen permeation curve is as follows Figure 2 As shown in 5#.

[0042] Example 2

[0043] This embodiment is substantially the same as embodiment 1, except that a 0.5 mol / L sulfuric acid solution is added to the cathode chamber. At this time, the measured electrochemical hydrogen permeation curve is as follows: Figure 2 As shown in 4#. Even if H + The concentration has increased by 5 times, and the hydrogen barrier coating effect is still excellent.

[0044] Comparative Example 1

[0045] Cut X80 pipeline steel into 20mm×20mm×1.5mm sheet samples, sand them to 2000# with sandpaper, clean the surface and dry it. Figure 3 (a) shown.

[0046] The experiment used a Davanathan-Stachursky double electrolytic cell. The sample was fixed between the cathode chamber and the anode chamber. The effective detection area was 1 cm 2 On the anode chamber side, a three-electrode system was used, with the sample as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the auxiliary electrode, connected to the electrochemical workstation by a wire; on the cathode chamber side, a two-electrode method was used, with the sample as the cathode and the platinum sheet as the anode.

[0047] During the experiment, 0.1 mol / L sodium hydroxide solution without dissolved oxygen was first loaded into the anode chamber, and the anode potential was controlled to be open circuit potential + 250 mV (relative to the reference electrode). When the background current measured in the anode chamber was less than 0.1 μA / cm 2 When the cathode chamber is filled with 0.1 mol / L sulfuric acid solution, a current of 10 mA / cm2 is applied between the positive and negative electrodes. 2 of current.

[0048] At this time, the measured electrochemical hydrogen permeation curve is as follows Figure 2 As shown in 1#.

[0049] Comparative Example 2

[0050] Cut X80 pipeline steel into 20mm×20mm×1.5mm sheet samples, sand them to 2000# with sandpaper, clean the surface and dry it. Then spray graphene oxide suspension on the surface of X80, dry it in an oven and set it aside. The concentration of the sprayed graphene oxide suspension is 8.5mg / mL; the oven drying temperature is 65℃, the time is 3 hours, and the coating thickness is 40-50μm. At this time, the obtained sample is as follows Figure 3 (b) as shown.

[0051] The experiment used a Davanathan-Stachursky double electrolytic cell. The sample was fixed between the cathode chamber and the anode chamber. The effective detection area was 1 cm 2 , the side with graphene oxide coating faces the cathode chamber. On the anode chamber side, a three-electrode system is used, with the sample as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the auxiliary electrode, connected to the electrochemical workstation by a wire; on the cathode chamber side, a two-electrode method is used, with the sample as the cathode and the platinum sheet as the anode.

[0052] During the experiment, 0.1 mol / L sodium hydroxide solution without dissolved oxygen was first loaded into the anode chamber, and the anode potential was controlled to be open circuit potential + 250 mV (relative to the reference electrode). When the background current measured in the anode chamber was less than 0.1 μA / cm2, 0.1 mol / L sulfuric acid solution was added to the cathode chamber, and a current of 10 mA / cm2 was applied between the positive and negative electrodes.

[0053] At this time, the measured electrochemical hydrogen permeation curve is as follows Figure 2 As shown in 3#.

[0054] Comparative Example 3

[0055] Cut X80 pipeline steel into sheets of 20mm×20mm×1.5mm, polish with sandpaper to 2000#, clean the surface and dry it. Then drip the electrocatalytic layer on the surface of X80, dry it in an oven and set it aside. Among them, the electrocatalyst powder is 6mg of MoC, add 1mL of isopropanol and water (volume ratio 9:1) dispersion, and then add 10μL of perfluorosulfonic acid polytetrafluoroethylene copolymer adhesive (concentration 5%) solution, ultrasonic oscillation power 120W, time 30min, oven temperature for drying the electrocatalyst layer is 60℃, time 2h, and the thickness of the electrocatalyst layer is 0.5~1.5μm. At this time, the obtained sample is as follows Figure 3 (c) as shown.

[0056] The experiment used a Davanathan-Stachursky double electrolytic cell. The sample was fixed between the cathode chamber and the anode chamber. The effective detection area was 1 cm 2, the side with the electrocatalyst layer faces the cathode chamber. On the anode chamber side, a three-electrode system is used, with the sample as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the auxiliary electrode, connected to the electrochemical workstation by a wire; on the cathode chamber side, a two-electrode method is used, with the sample as the cathode and the platinum sheet as the anode.

[0057] During the experiment, 0.1 mol / L sodium hydroxide solution without dissolved oxygen was first loaded into the anode chamber, and the anode potential was controlled to be open circuit potential + 250 mV (relative to the reference electrode). When the background current measured in the anode chamber was less than 0.1 μA / cm 2 When the cathode chamber is filled with 0.1 mol / L sulfuric acid solution, a current of 10 mA / cm2 is applied between the positive and negative electrodes. 2 of current.

[0058] At this time, the measured electrochemical hydrogen permeation curve is as follows Figure 2 As shown in 2#.

[0059] The present invention sets 5 groups of experiments, namely 1#, 2#, 3#, 4#, and 5#. The specific conditions of these 5 groups of experiments are shown in the specific implementation example 1, comparative example 2, comparative example 3, embodiment 1, and embodiment 2. The experimental results are as follows Figure 2 As shown, it can be seen that the steady-state segments of the curves are 2#, 1#, 3#, 4#, and 5# from high to low. Combined with the experimental conditions in the specific implementation method, it can be seen that the hydrogen atom penetration is from high to low: the sample with only the electrocatalyst layer, the sample without coating, the sample with only the conductive resistive hydrogen layer, and the sample with the conductive resistive hydrogen layer and the electrocatalyst layer, indicating that the hydrogen barrier coating involved in the present invention can effectively prevent hydrogen atoms from penetrating into the metal matrix. Comparing the electrochemical hydrogen permeation curves of 4# and 5#, it can be seen that the concentration of sulfuric acid solution in the cathode chamber increases by 5 times, and the hydrogen permeation curve only rises slightly, that is, the hydrogen atom penetration increases only a small amount, indicating that the hydrogen barrier coating involved in the present invention can still serve stably for a long time even in an environment with high "external hydrogen" concentration.

[0060] The hydrogen barrier coating involved in the present invention can effectively block hydrogen atoms from penetrating into the steel matrix for the following two reasons: ① The outermost electrocatalyst layer, under the action of the cathodic protection current, reduces the overpotential of the hydrogen evolution reaction and then electrolyzes water to produce hydrogen atoms. However, since the electrocatalyst used has the physical property of being difficult to adsorb and easy to desorb hydrogen atoms, most of the hydrogen atoms adsorbed on the surface of the coating are converted into hydrogen gas and desorbed, so that the concentration of hydrogen atoms on the surface of the coating is greatly reduced, that is, the concentration gradient of hydrogen atoms from the surface to the core is reduced, and the driving force for hydrogen atom penetration is reduced; ② The second outermost conductive hydrogen barrier layer is composed of one or more of two-dimensional materials such as graphene, graphene oxide, and reduced graphene oxide. This two-dimensional material is not only conductive, but also has physical properties that hydrogen atoms cannot directly penetrate. The multi-layer superposition makes the diffusion path of hydrogen atoms tortuous and extended, which greatly improves the diffusion activation energy of hydrogen atoms.

[0061] In addition, the hydrogen barrier coating designed by the present invention can be directly produced in the range of 55 to 75°C, which greatly simplifies the process and reduces energy consumption. In a water / wet service environment, it fully utilizes the existing cathodic protection technology, conforms to the conventional actual service environment of metal materials, and also reduces the difficulty of engineering transformation.

[0062] It should be noted that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A hydrogen barrier coating, characterized in that: The hydrogen barrier coating includes a first coating and a second coating sequentially formed on the surface of a metal substrate, wherein the first coating is composed of a stacked conductive two-dimensional material, wherein the conductive two-dimensional material includes one or more of graphene, graphene oxide, and reduced graphene oxide, and the second coating is prepared from an electrocatalyst powder, a dispersion, and a binder, wherein the electrocatalyst powder is a transition metal carbide.

2. The hydrogen barrier coating according to claim 1, characterized in that: The electrocatalyst powder is MoC or WC.

3. The hydrogen barrier coating according to claim 1, characterized in that: The dispersion is isopropyl alcohol or water or a mixture of the two.

4. The hydrogen barrier coating according to claim 1, characterized in that: The binder is a perfluorosulfonic acid polytetrafluoroethylene copolymer.

5. The method for preparing the hydrogen barrier coating according to claim 1, characterized in that: The steps include: Dispersing the conductive two-dimensional material in water to form a suspension, coating the suspension on the surface of the metal substrate, and drying to form a first coating; The electrocatalyst powder, dispersion and binder are mixed and coated on the surface of the first coating layer, and then dried to form a second coating layer.

6. The preparation method according to claim 5, characterized in that: The concentration of the suspension is 8-9 mg / mL.

7. The preparation method according to claim 5, characterized in that: The thickness of the first coating layer is 40-50 μm, and the thickness of the second coating layer is 0.5-1.5 μm.

8. The preparation method according to claim 5, characterized in that: The electrocatalyst powder mass and dispersion volume ratio is 5.5-6.5 mg:1 mL.

9. The use of the hydrogen barrier coating according to claim 1, characterized in that: The metal substrate prepared with the hydrogen barrier coating is connected to the cathodic protection system and the cathodic protection current is loaded.

10. The use according to claim 8, characterized in that The cathode protection current density is 10-50 mA / cm 2 .

Citation Information

Patent Citations

  • Stainless steel based hydrogen permeation prevention composite coating

    CN103802385A

  • Ternary composite novel hydrogen / deuterium / tritium permeation resistant coating and preparation method thereof

    CN115110067A

  • Preparation method of hydrogen permeation barrier layer on surface of high-strength steel

    CN116657102A

  • Preparation method of pipe fitting hydrogen permeation resisting composite coating

    CN116809360A

  • In-situ grown large size nanoplatelet reinforced and toughened hydrogen permeation barrier coating and method of making the same

    CN117701043B

Cited By

  • Ni-Zn-P-ZnO composite hydrogen-resistant coating and preparation method thereof

    CN121826827A